The impact of innovation, external financing, and business networks on msme growth - Dwi Ayuningrum, Ananda Puput; Ariani, Kurnia Rina (Institute of Computer Science (IOCS), 2025)
This study analyzes the influence of innovation, External Financing and business networks on the growth of Micro, Small and Medium Enterprises (MSMEs) in Sukoharjo Regency, Central Java. The research method used is quantitative with data collection techniques through questionnaires distributed to 101 respondents selected using the purposive sampling method. The results of the study indicate that innovation, External Financing, and business networks simultaneously and partially have a significant effect on MSME growth. The business network factor has the greatest influence, followed by innovation and External Financing. These findings underline the importance of collaboration, access to financing, and innovation in encouraging the sustainability and competitiveness of MSMEs